2008
DOI: 10.1002/jcc.21049
|View full text |Cite
|
Sign up to set email alerts
|

Formation pathways of DMSO from DMS‐OH in the presence of O2 and NOx: A theoretical study

Abstract: The relative importance of the reaction pathways and thus the product yields in the dimethyl sulfide (DMS) degradation scheme initiated by the hydroxyl (OH) radical has been said to be influenced by the content of nitrogen oxides (NO(x)) in chamber experiments. In this study, ab initio and density functional electronic structure calculations of all the possible reaction pathways corresponding to the reaction process initiated by DMS-OH + oxygen (O(2)), leading to the formation of the dimethyl sulfoxide (DMSO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…37,39 In those studies, the stationary points found were characterized at both the MPW1K/6-311G(d,p) and the MPW1K/MG3S levels of calculation. Those stationary points were connected by means of the corresponding MEPs calculated with the smaller basis set.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
See 3 more Smart Citations
“…37,39 In those studies, the stationary points found were characterized at both the MPW1K/6-311G(d,p) and the MPW1K/MG3S levels of calculation. Those stationary points were connected by means of the corresponding MEPs calculated with the smaller basis set.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…According to the conclusions obtained in a previous work 32 and maintaining the methodology used in our recent electronic structure studies, [37][38][39] the MPW1K/MG3S level of calculation has been chosen for the description of the PES. The selected MPW1K 28,42 (modified Perdew-Wang one-parameter model for kinetics) hybrid functional is based on the PerdewWang exchange functional with Adamo and Barone's modified enhancement factor and the Perdew-Wang correlation functional.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main gas‐phase degradation process of DMS in the troposphere is chemical oxidation initiated by OH radicals during the day and by NO 3 radicals at night. These processes lead to the formation of sulfur‐containing species, such as sulfuric and methane sulfonic acids, which can significantly contribute to the acidity of the atmosphere 2–5. It has been postulated that emissions of DMS from the oceans may have a significant influence on the Earth's radiation budget and possibly in climate regulation due to the formation of CCN (cloud condensation nuclei) from the oxidation of SO 2 formed in the photo‐oxidation of DMS 6–10.…”
Section: Introductionmentioning
confidence: 99%